Real-world disease activity and sociodemographic, clinical and treatment characteristics of moderate-to-severe inflammatory bowel disease in Brazil - Zaltman, Cyrla; Parra, Rogério Serafim; Sassaki, Ligia Yukie [UNESP]; Santana, Genoile Oliveira; de Lourdes Abreu Ferrari, Maria; Miszputen, Sender J.; Amarante, Heda M.B.S.; Kaiser, Roberto Luiz; Flores, Cristina; Catapani, Wilson R.; Parente, José Miguel Luz; Bafutto, Mauro; et al. (Baishideng Publishing Group, 2021)
BACKGROUND Understanding the treatment landscape of inflammatory bowel diseases (IBD) is essential for improving disease management and patient outcomes. Brazil is the largest Latin American country, and it presents socioeconomic and health care differences across its geographical regions. This country has the highest increase in IBD incidence and prevalence in Latin America, but information about the clinical and treatment characteristics of IBD is scarce. AIM To describe the sociodemographic, clinical, and treatment characteristics of IBD outpatients in Brazil overall and in the Southeast, South and Northeast/Midwest regions. METHODS Multicenter, cross-sectional study with a 3-year retrospective chart review component. Patients with moderate-to-severe Crohn's disease (CD) or ulcerative colitis (UC) were consecutively enrolled between October 2016 and February 2017. Active CD at enrollment was defined as a Harvey Bradshaw Index ≥ 8 or a CD Activity Index ≥ 220 or a calprotectin level > 200 μg/g or an active result based on colonoscopy suggestive of inadequate control during the previous year; active UC was defined as a partial Mayo score ≥ 5. Descriptive statistics were used to analyze all variables. RESULTS In a total of 407 included patients, CD was more frequent than UC, both overall (264 CD/143 UC patients) and by region (CD:UC ratios of 2.1 in the Southeast, 1.6 in the South and 1.2 in the Northeast/Midwest). The majority of patients were female (54.2% of CD; 56.6% of UC), and the mean ages were 45.9 ± 13.8 years (CD) and 42.9 ± 13.0 years (UC). The median disease duration was 10.0 (range: 0.5-45) years for both IBD types. At enrollment, 44.7% [95% confidence interval (CI): 38.7-50.7] of CD patients and 25.2% (95%CI: 18.1-32.3) of UC patients presented with active disease. More than 95% of IBD patients were receiving treatment at enrollment; CD patients were commonly treated with biologics (71.6%) and immunosuppressors (67.4%), and UC patients were commonly treated with mesalazine [5-Aminosalicylic acid (5-ASA)] derivates (69.9%) and immunosuppressors (44.1%). More than 50% of the CD patients had ileocolonic disease, and 41.7% presented with stricturing disease. One-quarter of CD patients had undergone CD-related surgery in the past 3 years, and this proportion was lower in the Northeast/Midwest region (2.9%). CONCLUSION In Brazil, there are regional variations in IBD management. CD outweighs UC in both frequency and disease activity. However, one-quarter of UC patients have active disease, and most are receiving 5-ASA treatment.
Keywords: Crohn's disease; Disease activity; Epidemiology; Inflammatory bowel disease; Treatment; Ulcerative colitis